2017
DOI: 10.1371/journal.pone.0188069
|View full text |Cite
|
Sign up to set email alerts
|

Vascular surgical stretch injury leads to activation of P2X7 receptors and impaired endothelial function

Abstract: A viable vascular endothelial layer prevents vasomotor dysfunction, thrombosis, inflammation, and intimal hyperplasia. Injury to the endothelium occurs during harvest and “back table” preparation of human saphenous vein prior to implantation as an arterial bypass conduit. A subfailure overstretch model of rat aorta was used to show that subfailure stretch injury of vascular tissue leads to impaired endothelial-dependent relaxation. Stretch-induced impaired relaxation was mitigated by treatment with purinergic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“… 49 P2X7-induced renal vasoconstriction causes tissue hypoxia, where along with inflammatory cytokines and reactive oxygen species, it causes inflammation, fibrosis, and glomerular dysfunction. 49 , 58 62 Together, renal fibrosis, increased sodium retention, and renal vasoconstriction promote a rise in blood pressure (BP) that can increase systemic circulating ATP concentrations. The resulting P2X7 activation promotes endothelial cell apoptosis, 67 , 68 vascular remodeling, and ultimately endothelial dysfunction, 62 , 71 which further exacerbates the increase in BP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 49 P2X7-induced renal vasoconstriction causes tissue hypoxia, where along with inflammatory cytokines and reactive oxygen species, it causes inflammation, fibrosis, and glomerular dysfunction. 49 , 58 62 Together, renal fibrosis, increased sodium retention, and renal vasoconstriction promote a rise in blood pressure (BP) that can increase systemic circulating ATP concentrations. The resulting P2X7 activation promotes endothelial cell apoptosis, 67 , 68 vascular remodeling, and ultimately endothelial dysfunction, 62 , 71 which further exacerbates the increase in BP.…”
Section: Discussionmentioning
confidence: 99%
“… 49 Prolonged exposure to elevated extracellular ATP results in P2X7-mediated mesangial, fibroblast, endothelial, and renal tubular cell death, contributing to renal inflammation and fibrosis, as well as promoting endothelial dysfunction. 58 62 P2X7 antagonism results in a partially NO-dependent vasodilation of the afferent, efferent, and renal arteries, increasing renal perfusion and reducing renal inflammation and fibrosis. 49 , 50 , 52 , 54 P2X7 KO (knockout) or antagonism has also proved effective in preventing renal fibrosis, renal immune cell infiltration, and lowering BP and albuminuria in Dahl salt-sensitive rats and in a deoxycorticosterone acetate–salt model of hypertension.…”
Section: P2x7 and Kidney Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…P2X7R aggravates LPS-induced vascular dysfunction and increases downstream production of inflammation [ 49 , 50 ]. Besides, P2X7R activation leads to endothelial dysfunction by impairing eNOS/NO signaling pathway [ 51 , 52 ]. However, there is insufficient evidence to suggest that P2X7R is involved in diabetes-induced endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings in our laboratory suggested that treatment of HSVEC with ATP, released after NS injury, reduces NO production [21]. NO production is regulated by synthesis (via activated eNOS) or substrate availability (via arginase).…”
Section: Resultsmentioning
confidence: 99%